Incidence, characteristics, maternal complications, and perinatal outcomes associated with preeclampsia with severe features and HELLP syndrome - Kongwattanakul K; Saksiriwuttho P; Chaiyarach S; Thepsuthammarat K (Dove Medical Press, 2018)
Kiattisak Kongwattanakul,1 Piyamas Saksiriwuttho,1 Sukanya Chaiyarach,1 Kaewjai Thepsuthammarat2 1Department of Obstetrics and Gynecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 2Clinical Epidemiology Unit, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand Objective: To determine the incidence of preeclampsia with severe features among pregnant women and evaluate the characteristics, maternal complications, and perinatal outcomes between nonsevere preeclampsia versus preeclampsia with severe features and hemolysis, elevated liver enzyme levels, and low platelet levels (HELLP) syndrome.Materials and methods: A retrospective descriptive study was conducted at Khon Kaen University’s Srinagarind Hospital, a tertiary care facility in northeast Thailand. The pregnant women who had been diagnosed with preeclampsia according to American College of Obstetricians and Gynecologists guidelines from January 1, 2012 to December 31, 2016 were identified and their medical records were reviewed. Various characteristics were examined to compare maternal complications and perinatal outcomes.Results: There was a total of 11,199 deliveries during the study period, out of which 213 preeclamptic women were identified. One hundred and seven women (9.6 per 1,000 deliveries) were diagnosed with nonsevere preeclampsia, 90 (8 per 1,000 deliveries) had preeclampsia with severe features, and 16 (1.4 per 1,000 deliveries) had HELLP syndrome. Twenty-one women (9.9%) experienced postpartum hemorrhage; 11 (10.3%) in the nonsevere features preeclampsia group and 10 (9.4%) in the preeclampsia with severe features and HELLP syndrome group. Placental abruption (3 women; 1.4%) and heart failure (1 women; 0.4%) only occurred among women in the preeclampsia with severe features group. Neonatal complications were significantly higher in the preeclampsia with severe features and HELLP syndrome group (low birth weight =35.1% versus 74.3%, p<0.001; birth asphyxia =4.4% versus 18.2%, p=0.001; neonatal intensive care unit admission =7.0% versus 30.9%, p<0.001; neonatal resuscitation =15.8% versus 42.7%, p<0.001). Stillbirths only occurred in cases of preeclampsia with severe features and HELLP syndrome (3 cases, 1.4%). Intrapartum death was higher in cases of preeclampsia with severe features and HELLP syndrome, but without statistical significance (2.6% versus 6.4%, p=0.190).Conclusion: The incidence of preeclampsia with severe features and HELLP syndrome was 9.5 per 1,000 deliveries. Severe maternal and perinatal outcomes were more commonly observed. Keywords: preeclampsia, HELLP syndrome, pregnancy induced hypertension, perinatal outcome, preeclampsia with severe features